Insulin Growth Factor Binding Protein 7 (IGFBP7)-Related Cancer and IGFBP3 and IGFBP7 Crosstalk - Jin, Li; Shen, Fan; Weinfeld, Michael; Sergi, Consolato (Frontiers in Oncology, 2020)
The insulin/insulin-like growth factors (IGFs) have crucial tasks in the growth, differentiation, and proliferation of healthy and pernicious cells. They are involved in coordinated complexes, including receptors, ligands, binding proteins, and proteases. However, the systems can become dysregulated in tumorigenesis. Insulin-like growth factor-binding protein 7 (IGFBP7) is a protein belonging to the IGFBP superfamily (also termed GFBP-related proteins). Numerous studies have provided evidence that IGFBP3 and IGFBP7 are involved in a variety of cancers, including hepatocellular carcinoma (HCC), breast cancer, gastroesophageal cancer, colon cancer, prostate cancer, among many others. Still, very few suggest an interaction between these two molecules. In studying several cancer types in our laboratories, we found that both proteins share some crucial signaling pathways. The objective of this review is to present a comprehensive overview of the relationship between IGFBP7 and cancer, as well as highlighting IGFBP3 crosstalk with IGFBP7 reported in recent studies.